Orientasi Studi Lanjut dan Karir Setelah Lulus Menggunakan Alat Ukur Tes Karir Online Bagi Siswa Kelas XII SMK Plus Al-Aitaam Bandung - Wijayanto, Pikir Wisnu; Qana'a, Mutia (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
Several obstacles occur on the part of the Counseling Guidance teacher at SMK Plus Al Aitaam Bandung. This factor happens because there is still a lack of knowledge from guidance counselors regarding materials on students' interests, talents, and information and knowledge about the various types of majors in tertiary institutions. Teachers still feel confused when dealing with students who need direction regarding their interests and talents. Especially when the students choose a major or related career description in work and business. Also, they could not use the test tool can be used to identify the interests and talents of these students. The purpose of this Community Service activity is to assist in the form of self-motivated training (workshop) in designing further studies and careers after graduation for class XII students. The measurement of their interests and talents uses a web-based online career test. The results of the implementation of the mentoring activities were considered very good by the partners. This web-based online interest test helps solve student problems. So that they feel that the activity material is following their needs. In addition, they can also identify interests and talents in determining the next step after graduation.